1993
DOI: 10.1038/364540a0
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of RabSB expression attenuates Ca2+-dependent exocytosis in rat anterior pituitary cells

Abstract: Low-molecular-weight GTP-binding proteins (small G proteins) of the Rab family have been proposed to act as central regulators of vesicular traffic, and proteins of the Rab3 subfamily (Rab3A, B, C and D) are thought to be associated with membrane vesicles or granules undergoing exocytotic fusion with the plasma membrane. Rab3A is highly expressed in brain, whereas Rab3B is the major form found in rat anterior pituitary gland. We report here that antisense oligonucleotides against Rab3B, introduced into pituita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
118
2

Year Published

1995
1995
2006
2006

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 201 publications
(123 citation statements)
references
References 34 publications
3
118
2
Order By: Relevance
“…rab3a) and facilitatory rab proteins (Frab) (e.g. rab3b and rab3d) [18,34,35]. Nevertheless, an explanation of how rab3AL would affect rab3a intracellular function and cause stimulation of exocytosis has been offered [23].…”
Section: Discussionmentioning
confidence: 99%
“…rab3a) and facilitatory rab proteins (Frab) (e.g. rab3b and rab3d) [18,34,35]. Nevertheless, an explanation of how rab3AL would affect rab3a intracellular function and cause stimulation of exocytosis has been offered [23].…”
Section: Discussionmentioning
confidence: 99%
“…The two forms of Rab protein are converted from one to the other by the action of GDP/GTP exchange factors and GTPase-activating proteins. While many Rab proteins are ubiquitously expressed, the Rab3 family proteins (Rab3A,Rab3B,Rab3C,and Rab3D) are enriched in the brain and secretory tissues, and have proven to be associated with Ca 2+ -regulated exocytosis in mammals (Lledo et al 1993;Fischer von Mollard et al 1994;Castillo et al 1997;Chen et al 2002). Rab3A, the best-characterized member of the Rab3 subfamily, is a predominant isotype present in neurons and amine/peptide-secreting endocrine cells, controlling calcium-dependent exocytosis as a positive or negative regulator (Holz et al 1994;Lledo et al 1994;Regazzi et al 1996;Takai et al 1996, Geppert andSudhöf 1998;Yaekura et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that SNAP-25 is essential in the regulated release of adrenocorticotropin (ACTH) and prolactin (PRL) from AtT-20 and GH3 cell lines respectively , Masumoto et al 1997. In addition, different members of the Rab family are involved in secretory granule localization and calciuminduced exocytosis in anterior pituitary cells (Lledo et al 1993, Nsee et al 1993, Perez et al 1994.…”
Section: Introductionmentioning
confidence: 99%